In vitro antifungal activities and phytochemical analysis of filamentous white-rot fungi, schizophyllum commune - Yi, Peng Teoh; Mashitah Mat Don (Universiti Kebangsaan Malaysia, 2013)
In this study, the in-vitro antifungal activity and phytochemical analysis of Schizophyllum commune extracts have been investigated. The antifungal activity was tested against 11 species of selected wood degrading fungi of rubberwood. The results showed that water, methanol and ethanol extracts significantly inhibited the growth of wood degrading fungi with minimum inhibitory concentration (MIC) ranges 0.16-5.00 μg/μL. P. sanguineus was found as the strongest wood degrading fungus where it required the highest concentration of S. commune crude extracts (≥ 5.00 μg/μL) to inhibit its mycelia growth. Phytochemicals analysis revealed that the extracts contained flavonoid, phenol and saponin. The methanol extracts of S. commune was then applied on the rubberwood blocks and found that the growth of P. sanguineus was inhibited effectively at 5.00 μg/μL.